Planning management and urban development: experience of EU, Germany and Vietnam (Seminar proceedings) (Hiệp hội các đô thị Việt Nam, 2006)
Cuốn kỷ yếu này được xuất bản với sự tài trợ của Viện Konrad Adenauer (CHLB Đức)